Survey of the semiaquatic bugs (Hemiptera: Heteroptera: Gerromorpha) from Alagoas and Sergipe, Northeast Brazil - Rodrigues, Juliana Mourão Dos Santos; Nery, Leticia; Rodrigues, Higor D. D.; Moreira, Felipe Ferraz Figueiredo (Zootaxa, 2021)
A survey of the semiaquatic bugs (Hemiptera: Heteroptera: Gerromorpha) from Alagoas and Sergipe, Northeast Brazil, is presented. Specimens have been obtained mainly during three expeditions carried out in 2018 and 2019. Individuals of 40 species, representing the following 18 genera and five families have been recorded: Brachymetra Mayr, 1865, Cylindrostethus Mayr, 1865, Limnogonus Stål, 1868, Neogerris Matsumura, 1913, Tachygerris Drake, 1957, Rheumatobates Bergroth, 1892, Halobatopsis Bianchi, 1896, Ovatametra Kenaga, 1942 (Gerridae); Lipogomphus Berg, 1879, Merragata White, 1877 (Hebridae); Hydrometra Latreille, 1797 (Hydrometridae); Mesovelia Mulsant & Rey, 1852 (Mesoveliidae); Husseyella Herring, 1955, Microvelia Westwood, 1834, Rhagovelia Mayr, 1865, Paravelia Breddin, 1898, Platyvelia Polhemus & Polhemus, 1993 and Stridulivelia Hungerford, 1929 (Veliidae). Alagoas and Sergipe have 35 and 31 new records, respectively. Rheumatobates trinitatis (China, 1943) and Rhagovelia plumbea Uhler, 1894 are recorded for the first time from Brazil.